Emergency peripartum hysterectomy - Singh, Alka; Hada, Meera; Yangzom, Kundu; GC, Anita (Nepal Journal of Obstetrics and Gynaecology, 2009)
Objectives: To review the incidence, risk factors, indications, outcomes, and complications of emergency peripartum hysterectomy performed after cesarean section and vaginal deliveries. Study design: A nine years retrospective study of all those cases who underwent peripartum hysterectomy at Patan Hospital from the year 1997 to 2005. Results: There were total 28 cases of emergency peripartum hysterectomy, 16 caesarean hysterectomies, and 12 postpartum hysterectomies, with the incidence of 1 per 1364 deliveries. The most common indication for hysterectomy was uterine atony (35.7%) followed by uterine rupture (25%). Average estimated blood loss was 1600 ml, average time from delivery to hysterectomy was 130 minutes, the most common post operative complication was unspecified fever and the average length of hospitalization was 11.17 days. There was only one maternal mortality with 32% maternal morbidity and four perinatal mortality. Conclusion: Peripartum hysterectomy is usually associated with significant maternal and fetal morbidity and mortality yet it remains a potentially life saving procedure. Timely decision to intervene is essential for the optimum outcome. Uterine atony is the leading indication for emergency hysterectomy performed followed by rupture uterus and morbid adherent placenta. Key Words: Caesarean hysterectomy; Peripartum hysterectomy; Postpartum hysterectomy doi:10.3126/njog.v1i2.2395 N. J. Obstet. Gynaecol Vol. 1, No. 2, p. 33-36 Nov-Dec 2006